The internal market and the spontaneity of peasant movements (Puno, 1950-1968) - Claverías, Ricardo (1978)
In this work I address the study of peasant movements in Puno in the period from 1950 to 1969; that is to say, when the external domain adopts new forms of exploitation, the hegemony of the fractions of the "dominant bloc" is reordered, and particularly in the south of Peru, industrial-mining development begins as a new axis that will invigorate the development of the Interior market. However, due to the type of structure, especially in the Andean zone, and the contradictory nature of that domain, the development of capitalism is going to be very slow and painful, as can be deduced from the exposition in the following sections.